Pengaruh Sertifikasi Guru, Profesionalisme, dan Disiplin Kerja Terhadap Kinerja Guru - Deka Dwi Susanti; Andi Kristanto; Kaniati Amalia (Jurnal Studi Guru dan Pembelajaran, 2025)
This study aims to analyze the influence of teacher certification, professionalism, and work discipline on teacher performance in Indonesia. Optimal teacher performance is a key factor in achieving national education goals, making it crucial to understand the factors that impact teacher performance. This research uses a literature review method by analyzing 20 relevant previous studies. The literature selection process involves studies conducted on teachers at the elementary to secondary school levels in Indonesia, published within the last 1–5 years. Data collection was conducted using keywords such as teacher certification, professionalism, work discipline, and teacher performance, with the results selected based on relevance and the quality of the research methodology. The findings of the study indicate that teacher certification, professionalism, and work discipline have a significant impact on teacher performance. Teacher certification has been shown to enhance teacher competence and motivation, which in turn positively affects the quality of teaching. High professionalism, including mastery of the subject, pedagogical skills, and continuous self-development, also significantly influences teacher performance. Work discipline, which includes punctuality, adherence to rules, and commitment to teaching duties, further supports the improvement of teaching quality and student learning outcomes. These three variables work together to enhance overall teacher performance, ultimately contributing to the achievement of better educational outcomes.